2020
DOI: 10.14740/wjon1270
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Gastrointestinal Stromal Tumor as a Gateway for Streptococcus anginosus Causing Multiple Liver Abscesses

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common type of mesenchymal neoplasm of the gastrointestinal tract but consist of only 1% of all primary gastrointestinal neoplasms. Differentiated from other spindle cell tumors, GISTs are uniquely positive for CD117 expression which allows for molecular targeting therapy with imatinib mesylate (Gleevec). Clinical presentations are variable, ranging from asymptomatic to vague symptoms of abdominal pain, early satiety, abdominal distention or gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…This is particularly true for representatives of the Streptococcus genus. Many of the streptococcal species identified here are members of the viridans group Streptococci , a diverse group that has members associated with disease and polymicrobial infection (e.g., S. anginosus , associated with liver and soft tissue abscesses) ( Conte et al 2020 ), as well as members that have been proposed for use as probiotics (e.g., S. salivarius ) ( Shen et al 2014 ; Riaz Rajoka et al 2017 ). We recently found that the translocation of oral bacteria to the gut may lead to systemic inflammation during disease pathogenesis, including liver cirrhosis, and rifaximin treatment may prevent this oralization, thereby improving disease symptoms, including hepatic encephalopathy ( Patel et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for representatives of the Streptococcus genus. Many of the streptococcal species identified here are members of the viridans group Streptococci , a diverse group that has members associated with disease and polymicrobial infection (e.g., S. anginosus , associated with liver and soft tissue abscesses) ( Conte et al 2020 ), as well as members that have been proposed for use as probiotics (e.g., S. salivarius ) ( Shen et al 2014 ; Riaz Rajoka et al 2017 ). We recently found that the translocation of oral bacteria to the gut may lead to systemic inflammation during disease pathogenesis, including liver cirrhosis, and rifaximin treatment may prevent this oralization, thereby improving disease symptoms, including hepatic encephalopathy ( Patel et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%